Challenges micro-enterprises experience in accessing support information using e-Government websites: Case of the Western Cape - Osman, Muhammad Ameer (Department of Information Systems, 2018)
Background: Governments often provide support to Small, Medium and Micro-sized Enterprises (SMMEs) to ensure that they are sustainable. Micro-enterprises play an important role in the economic and socio-economic development of developing countries. However, the majority of micro-enterprises find it challenging to survive or to grow due to numerous challenges they experience. Information and Communication Technologies (ICTs) could assist micro-enterprises to grow and be competitive. E-Government has been internationally advocated to improve the delivery of government information. However, African governments are experiencing challenges that limit the success of e-Government. This has resulted in limited accessibility. Purpose of the research: The objective of the study is to investigate the challenges that micro-enterprises experience in accessing support information using e-Government websites in a developing country context. To achieve that the study describes the challenges experienced, analyses the types of support information accessed and identifies the Information and Communication Technology devices used to access support information. Design/methodology/approach: This multidisciplinary study adopted a constructivist approach and used an interpretive paradigm. The study was guided by Sen’s Capability Approach as a theoretical framework, and thematically analysed patterns between context, capabilities and outcomes. Data for the study was collected using semi-structured interviews. Furthermore, annual reports, published statistics and additional documents were also used as secondary data. Purposive and snowballing sampling were used to target established micro-enterprises in the Western Cape, South Africa. Findings: Micro-enterprises gained several benefits of using ICT for general business activities. These included improved access to information, improved communication, improved marketing, reduced costs and improved efficiency and productivity. Microenterprises also experienced several challenges with accessing support information using e-Government websites. These included content, structure, design, language availability and red tape. Support information relating to business skills development, products and services development and funding were mostly accessed. Furthermore, micro-enterprises mostly used laptops and mobile phones to access support information. Practical implications: The findings indicate that if micro-enterprises could access support information using e-Government websites, it could have a positive impact on their businesses such as improved competitiveness. Finally, the study uncovered that access to support information could also have a positive impact on the personal agency of microenterprises i.e. personal objectives such as women empowerment. Originality/contribution: The study contributes to the gap in research in terms of investigating the phenomenon of e-Government accessibility in developing countries. The study also contributes new understanding by separating the ICT and e-Government into two commodities to identify and show where the accessibility problem emanates from. Furthermore, the study proposes a conceptual model that provides an opportunity for researchers to understand users such as micro-enterprises of Government-to-Business projects so that suitable recommendation on the next course of actions be proposed to relevant stakeholders of future Government-to-Business projects.